Symbolic Meaning in the Traditional Dance of Bugis Makassar, Pakarena Dance (A Semiotic Study) - Asyrafunnisa Asyrafunnisa (Tamaddun Life, 2021)
This research aims to find the function and symbolic meaning of Pakarena Dance in Bugis Makassar society which is the dance movements represented the principal life. The research was conducted in South Sulawesi, Makassar. The data were collected from Library Research. The researcher used descriptive qualitative methods. The research showed the four functions of Pakarena Dance; (1) King's accompaniment (2) The means of Da'wah through its movements (3) The form of Gratitude (4). Entertainment Facilities. And Pakarena Dance has 13 parts symbolic meaning; (1). “Samboritta” (making friends) (2). Jangang leak-leak (rooster crows) (3). Ma'biring kassi(4). Bisei ri lau '(rowing to the east) (5). Angingkamalino (wind without blowing) (6). Anni-anni (spinning yarn) (7). Dalle tabbua (enduring fate patiently) (8). Nigandang (repeatedly) (9) So'nayya (dreaming) (10). Iyolle ', (looking for the truth) (11). Lambassari (disappointment) (12). Leko 'bo'dong(13). Sanro beja '(birth shaman). In this case, sign, idea and object have relation to show the symbolic meaning of Pakarena Dance.